Hubungan Berat Badan, Lila Dan Tekanan Darah Pada Ibu Terhadap Kejadian BBLR Di PMB Lina, Menteng Atas, Jakarta Selatan Tahun 2021 : The Relationship of Weight, Lila, and Blood Pressure in Mothers on the Incidence of BBLR in PMB Lina, Menteng Atas, South Jakarta in 2021 - Aritonang, Tiarlina (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: According to the World Health Organization (WHO), low birth weight (LBW) is defined as a birth weight of less than 2500 g regardless of gestational age. It is an important marker of maternal, fetal and nutritional health.3 Globally, it is estimated that 15% of all births are LBW, representing more than 20.5 million births a year.4 Most LBW births occur in low- and middle-income countries. WHO in 2020 there are 2.4 million children who die in the first month of a child's life. Around 6,700 babies die at birth every day, even 47% of them die before the age of 5 years. Sub-Saharan Africa has a neonatal mortality rate of 27 (25-32) deaths per 1000 live births. The prevalence of low birth weight is estimated at 15% worldwide with a range of 3.3 to 38% and mostly occurs in developing countries. Disability in infancy, childhood, even morbidity and even death is one of the factors of Low Birth Weight. LBW can even have a long impact on health into adulthood. The consequences of poor nutritional status and inadequate nutritional intake for women during pregnancy not only directly affect women's health status, but also have a negative impact on birth weight and early development. Lack of nutritional intake in mothers during pregnancy, can be one of the causes of births in babies with a baby's birth weight. Low Birth Weight (LBW) is the highest contributor to infant mortality. Methods: This research is descriptive using cross sectional method which aims to obtain information about the relationship between body weight and blood pressure of pregnant women with the incidence of LBW by using medical records with samples using a total sampling of 120 pregnant women. Results: Statistical test results obtained p value 0.007, known p value > 0.05, which means that there is no significant relationship between weight gain and the incidence of LBW. LILA and LBW also have no relationship with the p value of 0.296, and the statistical test results obtained a p value of 1,000. It is known that the p value > 0.05, which means that there is no significant relationship between blood pressure and the incidence of LBW. Discussion: Although the results do not show a relationship between the three variables with low birth weight, this is because there are factors that help, namely the mother's adherence to taking 120 tablets of Fe during pregnancy, thus helping the mother in maintaining physical health for pregnant women.